2000
DOI: 10.1093/ps/79.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Does excess dietary protein improve growth performance and carcass characteristics in heat-exposed chickens?

Abstract: The effects of two environmental temperatures (22 and 32 C, constant) and five dietary protein contents (10 to 33% CP) were investigated in 4- to 6-wk-old broiler chickens. High ambient temperature reduced growth rate, feed efficiency, and breast muscle proportion and increased abdominal fat proportion. Irrespective of ambient temperature, increasing dietary protein content improved growth performance and carcass characteristics. At 32 C, there was a greater heterogeneity of the data, and bird responses were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 22 publications
6
30
0
11
Order By: Relevance
“…Estes resultados estão de acordo com os descritos por Temim et al (2000), que, criando frangos de corte sob condições de estresse por calor, observaram redução na porcentagem do músculo do peito e aumento dos músculos das pernas. Ainda de acordo com esses autores, estes resultados podem ser pelo fato de que a musculatura do peito apresenta metabolismo glicolítico (fibras brancas) e a das pernas, metabolismo oxidativo (fibras vermelhas).…”
Section: Resultsunclassified
“…Estes resultados estão de acordo com os descritos por Temim et al (2000), que, criando frangos de corte sob condições de estresse por calor, observaram redução na porcentagem do músculo do peito e aumento dos músculos das pernas. Ainda de acordo com esses autores, estes resultados podem ser pelo fato de que a musculatura do peito apresenta metabolismo glicolítico (fibras brancas) e a das pernas, metabolismo oxidativo (fibras vermelhas).…”
Section: Resultsunclassified
“…This reduction in FI in turn decreases AA consumed. Therefore, some authors (Alleman and LeClercq, 1997;Temim et al, 1999Temim et al, , 2000 recommended higher AA under such environment. However, our current findings showed that feeding broilers with diets containing AA higher than the requirements under hot and humid condition is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…As to dietary protein concentration, two strategies are suggested to minimize CHS effects on growth rate: a) the use of low-protein diets in order to decrease heat increment, with some authors recommending lowering dietary protein content with the supplementation of essential amino acids (Waldroup, 1976;Austic, 1985;Cheng et al, 1997); and b) the use of high-protein diets to compensate lower feed intake caused by heat, as recommended by Temim et al (2000).…”
Section: Introductionmentioning
confidence: 99%